The Moral Imagination of Patricia Werhane: A Festschrift (Eminent Voices in Business Ethics ;, 2018)
This book celebrates the work of Patricia Werhane, an iconic figure in business ethics. This festschrift is a collection of articles that build on Werhane's contributions to business ethics in such areas as Employee Rights, the Legacy of Adam Smith, Moral Imagination, Women in Business, the development of the field of business ethics, and her contributions to such fields as Health Care, Education, Teaching, and Philosophy. All papers are new contributions to the management literature written by well-known business ethicists, such as Norman Bowie, Richard De George, Ronald Duska, Edwin Hartman, Michael Hoffman, Mollie Painter-Morland, Mark Schwartz, Andrew Wicks, and others. The volume is comprised of articles that reflect on Werhane's work as well as build on it as a way to advance further research. At the end of the festschrift, Pat Werhane provides responses to each chapter. The first chapter of the book also includes the overview of Patricia Werhane's work and her academic career. The book is written to appeal to management scholars and graduate students interested in the areas of Business Ethics, Modern Capitalism, and Human Rights. Patricia Werhane is one of the most distinguished figures in the field of business ethics. She was a founder of the field, she is one of its leading scholars, and she has had a profound impact on the world of business practice. Among her many accomplishments, Pat is known for her original work on moral imagination, she is an acclaimed authority on employee rights in the workplace, and she is one of the leading scholars on Adam Smith. Having been active in Academia for over 50 years, Werhane is a prolific author of over a hundred articles and book chapters, and the author or editor of twenty-seven books, including Adam Smith and his Legacy for Modern Capitalism, Moral Imagination and Management Decision-Making, and co-authored books Organization Ethics in Health Care, Alleviating Poverty Through Profitable Partnerships, Obstacles to Ethical Decision-Making, Corporate Responsibility: The American Experience, and Research Approaches to Business Ethics and Corporate Responsibility.